Liquid-phase atomic layer deposition of crystalline hematite without post-growth annealing. Issue 28 (25th June 2019) - Taniguchi, Asako; Taniguchi, Takaaki; Wagata, Hajime; Katsumata, Ken-ichi; Okada, Kiyoshi; Matsushita, Nobuhiro
Abstract : We carried out the liquid phase-atomic layer deposition (LP-ALD) of α-Fe2 O3 . The deposition temperature (95 °C) and rate (6.3 nm min −1 ) are much lower and higher than those offered by cutting edge gas-phase ALD techniques, respectively. Abstract : Owing to its cost-effectiveness and low-energy consumption, solution-processing of functional metal oxide films has been extensively studied over the past few decades. However, direct-solution routes to crystalline hematite (α-Fe2 O3 ) films without post-heat treatment have not been explored yet. This is because the solution-processing of these films involves the preferential formation of other iron oxides, hydroxides, and oxyhydroxides during the conventional precipitation reactions. Herein, we developed a direct-growth route for the preparation of crystalline α-Fe2 O3 using the spin spray (SPS) technique. We carried out the liquid phase-atomic layer deposition (LP-ALD) of α-Fe2 O3 . The mechanism involved the surface adsorption of Fe 2+ followed by the oxidization and formation of Fe 3+ –O 2− bonds. The LP-ALD approach facilitated the low-temperature direct growth of highly crystalline, dense, and uniform α-Fe2 O3 films at 95 °C with a high deposition rate of 6.3 nm min −1 . The deposition temperature and rate are much lower and higher than those offered by cutting edge gas-phase ALD techniques (230 °C and 1.3 × 10 −2 nm min −1 ), respectively. Furthermore, the effects of the growth conditions on the formation and microstructure of the products were investigated in detail in order to elucidate the LP-ALD mechanism.